TACkling Cancer by Targeting Selective Protein Degradation - María del Mar Noblejas-López; David Tébar-García; Raquel López-Rosa; Ana Alcaraz-Sanabria; Pablo Cristóbal-Cueto; Alejandro Pinedo-Serrano; Lorenzo Rivas-García; Eva M. Galán-Moya (MDPI AG, 2023)
Targeted protein degradation has emerged as an alternative therapy against cancer, offering several advantages over traditional inhibitors. The new degrader drugs provide different therapeutic strategies: they could cross the phospholipid bilayer membrane by the addition of specific moieties to extracellular proteins. On the other hand, they could efficiently improve the degradation process by the generation of a ternary complex structure of an E3 ligase. Herein, we review the current trends in the use of TAC-based technologies (TACnologies), such as PROteolysis TArgeting Chimeras (PROTAC), PHOtochemically TArgeting Chimeras (PHOTAC), CLIck-formed Proteolysis TArgeting Chimeras (CLIPTAC), AUtophagy TArgeting Chimeras (AUTAC), AuTophagosome TEthering Compounds (ATTEC), LYsosome-TArgeting Chimeras (LYTAC), and DeUBiquitinase TArgeting Chimeras (DUBTAC), in experimental development and their progress towards clinical applications.